Messianic Sign in Wedding at Cana: Revealed God’s Glory and Leads Jesus' Disciples to Faith Narrative Reading of John 2,1-12 - Halek Bere, Paulus (Proceedings of The International Conference on Theology, Religion, Culture, and Humanities, 2024)
The story of the miracle of the wine in wedding at Cana is one of the most significant narrative text in the New Testament. Jesus did his first sign at the beginning of his public ministry. This study of the account of the wedding at Cana in Jn 2,1-12 is influenced by two statements “he revealed his glory and his disciple believed in him (v.11). I will approach the text by analyzing the characterization of every character in the narrative: how the character works to contribute to the theological perspective of the Gospel? The literary structure of the periscope is analyzed, and the meaning of the sign is understood as a Messianic miracle that leads the disciples to a firm belief in Jesus as the Messiah. It is argued that the revelation of glory does not create faith directly but it is link with the faith that the secret is only reveled to those who believe. The miracle of the wine is then able to reveal a profound secret concerning the person of Jesus, his union with the Father. The faith of the disciple in this text is not only an initial faith but a total faith in Jesus.